The NHT Cooperative Learning Model to Improve Pupils Learning Motivation in Primary School - Istiyati, Siti; Dakir, A; Poerwanti, Jenny Is (Universitas Negeri Makassar, 2014)
The purpose of this study are to improve students’ motivation by using model of NHT cooperative learning in the grade students’ of grade IV SDN 02 Doplang, through the use of NHT type cooperative model. The form of the research is action research. Data collection used questionnaires and observation techniques. The data analysis technique used is an interactive model of Miles and Huberman. Based on the results of this study concluded that the using of cooperative learning model NHT type can increase the motivation of students. In the pre-action obtain by the average students’ motivation 60,88, cycle first for 72,80, cycle II for 84,20.